Trade beyond Doha - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2011)
Focusing on the Least Developed Countries located in the Asia-Pacific region, this study explores the impact of different approaches available to the LDCs and their partners in improving their developmental prospects through enhanced trade. It presents trade related data of the 14 LDCs and the linkage between trade and economic development. It analyses market access and studies increasing protectionist measures faced by LDCs during the crisis period. It explores reciprocal trade liberalization policies (bilateral, plurilateral and multilateral) from various perspectives in order to better understand their differences, interaction and impact on LDCs and more developed countries. It also discusses possible options to improve the capacity of LDCs to tap their trade potential and integrate more effectively into the global economy.